Key concepts in Eastern philosophy - Leaman, Oliver (Routledge, 1999)
Key Concepts in Eastern Philosophy provides an extensive glossary of the main terms and concepts used in Eastern philosophy. The book includes definitions of philosophical ideas linked to the national traditions of: * Persia * India * Islamic world * China * Japan * Tibet including concepts from: * Zoroastrianism * Hinduism * Sufism * Islam * Confucianism * Shintoism * Taoism * Buddhism Each entry includes a guide for further reading and critical analysis, and is cross-referenced with associated concepts and is in easy-to-use A-Z format.